Marcomannic wars and new Roman period discoveries in Jevíčko (West Moravia/East Bohemia) - Eduard Droberjar (Archeologické Rozhledy, 2020)
The paper deals with the issue of Roman archaeological finds and assemblage in the Malá Haná region in the context of substantial strong Germanic settlement activities that had or may have had connections to the period of Marcomannic wars. During the last decade of research in particular on sites near Jevíčko town in was possible to gain a lot of knowledge on the issues of settlement of the Early Roman period. In addition to Roman imports, related to trade activities, a whole range of artifacts (especially militaria) can be associated with the movement of the Roman army deep in the Barbaricum or directly with the northernmost Roman temporary camp near Jevíčko. The Malá Haná region thus becomes an important research area for a detailed interpretation of Roman-Germanic interactions at the end of the reign of Emperor Marcus Aurelius.